Pengaruh Pengetahuan Investasi, Kebijakan Modal Minimal, Pelatihan Pasar Modal terhadap Minat Mahasiswa Berinvestasi - Sindi Pramita Sari; Wiwik Lestari (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Investment interest is the desire to place some of the funds that are intentionally accommodated in the capital market for future profits. This study aims to examine the effect of investment knowledge, minimum capital policy, capital market training on students interest in investing. The number of respondents from this study were 133 respondents who came from Surabaya with the criteria as FEB faculty students at tertiary institutions in Surabaya and had attended capital market training or investment seminars at least once. The method used in this research is purposive sampling. The analysis technique used in this study is Partial Least Square Equation Modelling by usingsoftware Warp-PLS 8.0. The results of this study prove that investment knowledge has a not significant positive effect on investment intention, minimum capital policy and capital market training have a significant positive effect on investment intention.